The Effect Of Different Temperature On Survival Rate And P38 Mapk (Mytogen Activity Protein Kinase) Of Pangasius Djambal - Saputra Fredo; Maheno Sri Widodo; Eric Armando (Universitas Tidar, 2020)
The low survival value of seedlings is due to stress. Naturally cells in fish respond to the presence of environmental stressors by producing stress proteins such as mitogen-activated protein kinases (MAPKs). MAPKs are one of the important cellular signaling systems in fish as a response to the presence of environmental stressors. This study uses a completely randomized design method, 3 treatments 3 replications. The treatments given were (A) 28 o C temperature treatment, (B) 30 o C temperature treatment, (C) 32 o C temperature treatment, observations made were measurements of p38 mapk levels, survival and physical and chemical parameters. From observations of tissue staining (p38 MAPK) in the above table shows that the best results obtained in treatment B (30 o C) because there are many negative MAPK, so that at experience 30 o C the fish did not significant stress, and the highest survival rate was 83.3 %.